New species and new reports of Hyalella (Crustacea, Amphipoda, Dogielinotidae) from Argentina - Santos, Ana Lucia Freitas Dos; Araujo, Paula Beatriz; Bond-Buckup, Georgina (Zootaxa, 2008)
The genus Hyalella includes about 51 species, which occur only in the Americas. At present, 7 species are recorded from Argentinean hydrographic basins. Collections in streams in Argentina made during the years 2001, 2004, and 2005 revealed the presence of several species of Hyalella. The occurrence of H. araucana in the Province of Santa Cruz was confirmed. The distribution of H. kochi, previously recorded in Chile, Peru, and Bolivia, was extended to the provinces of Jujuy and Tucumán. A new species was found in the Province of Buenos Aires, and is described here. These new records increase from 7 to 9 the number of species known from Argentina and the Falkland Islands.